2016
DOI: 10.1111/apa.13565
|View full text |Cite
|
Sign up to set email alerts
|

Pilot manikin study showed that a supraglottic airway device improved simulated neonatal ventilation in a low‐resource setting

Abstract: AimWe compared the performance of personnel in a low‐resource setting when they used the I‐gel cuffless neonatal laryngeal mask or a face mask on a neonatal airway management manikin.MethodsAt Mulago Hospital, Uganda, 25 doctors, nurses and midwives involved in neonatal resuscitation were given brief training with the I‐gel and face mask. Then, every participant was observed positioning both devices on three consecutive occasions. The success rate and insertion times leading to effective positive pressure vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Sachs’ Children and Youth Hospital, Stockholm, Sweden, approved the study. Further ethical approval was not considered necessary for this study as it focused on the accuracy and speed of the method and not on comparing performance between individual participants or groups of participants, similar to a previously published manikin study . The participants gave oral consent to participate and could decline participation at any time during the study.…”
Section: Methodsmentioning
confidence: 99%
“…Sachs’ Children and Youth Hospital, Stockholm, Sweden, approved the study. Further ethical approval was not considered necessary for this study as it focused on the accuracy and speed of the method and not on comparing performance between individual participants or groups of participants, similar to a previously published manikin study . The participants gave oral consent to participate and could decline participation at any time during the study.…”
Section: Methodsmentioning
confidence: 99%
“… 17 All these characteristics make the cuffless LMA a potentially useful alternative to FM and endotracheal intubation, especially in settings where the staff skills in performing PPV are insufficient. 15 In a previous manikin study conducted in a low-resource setting, we found that the LMA was more effective than FM in establishing PPV, 18 but there are no published randomised trials comparing the LMA with the FM during neonatal resuscitation.…”
Section: Introductionmentioning
confidence: 95%
“…The training module for supraglottic airway use can easily be integrated to current neonatal resuscitation programs [33]. The cost-effectiveness of a supraglottic airway in a low-resource setting needs to be assessed.…”
Section: Methodsmentioning
confidence: 99%
“…A manikin study in Uganda demonstrated that midwives could easily insert a cuffless supraglottic airway after brief on-the-job training: the i-gel ® was also more effective than FM in establishing PPV in the manikin. In 2015, a phase II randomized controlled trial (RCT) on the same site demonstrated that midwives could effectively and safely perform resuscitation in neonates with the i-gel ® [32, 33].…”
Section: Introductionmentioning
confidence: 99%